(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2012)
The article deals with the analysis of Ukrainian folk counting-out rhymes with respect to their linguostylistic aspect. The author characterizes their genre, rhythmic, metrical, lexical, stylistic and grammatical peculiarities.